THE EFFECT OF ONLINE LEARNING ON STUDENT LEARNING OUTCOMES AT UPBJJ UT MEDAN - Hernawi Silalahi; Johannes Johannes (Sensei International Journal of Education and Linguistic, 2021)
The Covid 19 pandemic that has hit parts of the world, has affected and entered the State of Indonesia and changed the social fabric in our country. Education, which initially went well through face-to-face, now has to be done online. This situation requires educators including lecturers to be more responsive to the existing conditions. Students and lecturers who were initially less familiar with the online learning model, Kina had to be "forced" to respond to very sophisticated technology. This study aims to see to what extent the effect of online learning on student learning outcomes at UPBJJ UT Medan.This type of research is a quasi experiment (quasi-experimental). Based on the results of data analysis obtained; (1) The results of student learning in online learning obtained an average value of 79.13, (2) The results of learning conducted online obtained an average value of 72.41, (3) Therea significant effect of the use of online learning on student learning outcomes.